Study on Announcement Effect of Stock Repurchase from the Perspective of Configuration Analysis - Hong Bing Wang; Ai Hua Jin; Hai Yun Yu (Advances in Mathematical Physics)
This paper takes the stock repurchase cases in 2018-2019 after the promulgation of the New Company Law as the research object. Using the qualitative comparative analysis method and PSO-ICA-GARCH model, we analyze the influencing factors of the stock repurchase announcement market reaction. Through the analysis of the degree of premium (DP), repurchase ratio (RR), natural logarithm of total assets (LAS), return on net assets (ROE), top 10 shareholder equity ratio (CR10), and executive shareholding ratio (MSL), it is found that the paths of high CAR stock repurchase effect include repurchase clause-oriented type and centralization-proportional matching type; the path of nonhigh CAR stock repurchase effect includes size-premium limit type, profit-proportion limit type, and repurchase clause limit type. Compared with GARCH model, it has higher separation accuracy and more accurate model prediction effect.